Intrathecal neostigmine for postoperatrive analgesia in caesarean section - Hye, MA; Masud, KM; Banik, D; Haque, MF; Akhtaruzzaman, KM (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):586-93 The abstract of this article is available on the PubMed website